2016
DOI: 10.2147/ott.s99717
|View full text |Cite
|
Sign up to set email alerts
|

CT-diagnosed severe skull base bone destruction predicts distant bone metastasis in early N-stage nasopharyngeal carcinoma

Abstract: Bone metastasis is the most frequent type of distant metastasis in nasopharyngeal carcinoma (NPC). In this study, we investigated the correlation between the skull base bone destruction and the distant bone metastasis in patients with NPC. A total of 449 cases with NPC who were diagnosed and had definitive radiotherapy from 2001 to 2006 were enrolled in this study. The skull base bone destruction was diagnosed by computed tomography (CT) in all cases, and 191 patients also underwent magnetic resonance imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…There are certain characteristics specific to pediatric NPC that are markedly different from the adult population: being pediatric NPC is often classified as undifferentiated carcinoma, advanced loco-regional disease in the first diagnosis, higher prevalence of distant metastasis and closely associated with Epstein-Barr virus (EBV) etiology, and higher prevalence of treatment/therapy-related complications in comparison to the adult group [6,15]. MRI is usually helpful to provide accurate imaging for detecting perineural and intracranial spread and also accurate in detecting the marrow infiltration whereas cortical destruction of bone is better assessed by CT scan [16]. Both imaging are almost of the same accuracy for assessing the lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…There are certain characteristics specific to pediatric NPC that are markedly different from the adult population: being pediatric NPC is often classified as undifferentiated carcinoma, advanced loco-regional disease in the first diagnosis, higher prevalence of distant metastasis and closely associated with Epstein-Barr virus (EBV) etiology, and higher prevalence of treatment/therapy-related complications in comparison to the adult group [6,15]. MRI is usually helpful to provide accurate imaging for detecting perineural and intracranial spread and also accurate in detecting the marrow infiltration whereas cortical destruction of bone is better assessed by CT scan [16]. Both imaging are almost of the same accuracy for assessing the lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…The clivus of the skull base is one of the most common sites of NPC recurrence. [ 17 ] DWI is used for a variety of cancers, but few data are available for NPC. Therefore, this study aimed to investigate the DWI features of recurrent NPC after radiotherapy, and ADC thresholds for the diagnosis of recurrent NPC.…”
Section: Discussionmentioning
confidence: 99%
“…( 13 ) studied 518 LA-NPC patients and found that those with skull base invasion (SBI) had a higher risk of bone metastasis than those without (16.4% vs. 6.6%, respectively; P < 0.05). Other studies have shown that SBI detected by computed tomography (CT) was predictive of bone metastasis in patients with early N-stage NPC [2.478 (1.146–5.358), P = 0.021] ( 14 ). However, more research is needed to determine the independent prognostic value of SBI to the risk of bone metastasis.…”
Section: Introductionmentioning
confidence: 99%